Health and cleanliness : a text book for teachers - Green, George H. (George Henry), 1881- ; Buchan, G. F.; Muir, W. A. (London : Health and Cleanliness Council)
1938-03 1938 1930s 69 pages : illustrations 12 HEALTH AND CLEANLINESS (b) Because they wish to be like other people whom they love or admire. (c) Because they feel proud of being clean, and superior to people who are not. (d) Because of the real pleasure of feeling clean. (e) Because they view dirt with disgust. (f) Because being clean is associated with certain privileges, and being dirty with penalties or deprivations. (g) Because they believe that cleanliness is rewarded with certain material advantages. (h) Because they know of the relation between personal cleanliness and personal health, and desire good health. (i) Because they know the danger of dirt to the community, and believe that personal cleanliness is a duty which men owe to their neighbours. Clearly these motives vary widely in character. Some of them are closely related to instinctive tendencies, such as self-assertion, imitation, and repugnance. Others involve such relations between the child and other people as love, fear, or respect. Some, again, are in close relation to thought and experience, involving intelligence; whilst the last is distinctly moral in character. It is only the teacher of older children who may confidently make a lofty moral appeal to his pupils, or expect a reasonable practice of cleanliness to be related to scientific knowledge. The teacher of infants will necessarily content herself with appeals which do not demand so high a development on the part of the pupils. But in no case should it be forgotten that very few, if any, of our fixed attitudes and habits are based upon single motives, but that in any one of them a number of simple motives combine together, mutually reinforcing one another. The teacher will therefore increase the effectiveness of his work by giving as many motives as possible for the practice of personal cleanliness; not necessarily in a single lesson, but through the whole series, 177/5/8/3